Coping mechanics of progressive print media in Panay Island. - Hojilla, Kate Aubrey G.
This undergraduate thesis aims to find out the coping mechanisms of progressive print media in Panay Island. specifically, this will trace the history of Panay's progressive organizations, determine the five most widely used progressive print media, find out the coping mechanisms and analyze the trends, changes, and adjustments that progressive organizations incorporate in their print media during crucial periods in Philippine history such as the Pre-Martial Law, Martial Law, and Post-Martial Law times., This undergraduate thesis found out that progressive print media have evolved significantly since they were used by progressive forces as propaganda materials to maintain the growth of their organizations and ideology. Over the crucial periods in history, the progressive print media have steadily adapted to the changing preferences of the reading public. They have incorporated almost limitless changes in its structure and style of writing in order to gain more impact to its readers and, at the same time, compete with their mainstream print media. However, it is notable that the essence of content and intent of progressive print media were never altered. Eleven progressive organizations in Panay Island were involved in this study. Samples of progressive print media released since the Pre-Martial Law times were gathered and studied in this undergraduate thesis. This undergraduate thesis offers an analysis of progressive print media, a form of alternative media which exist since the early 1960s and continue to persist in recent times in Panay Island.